Comparison of three different regimens of oral azithromycin in the treatment of acne vulgaris - Naieni Farahnaz; Akrami Hooman (Wolters Kluwer Medknow Publications, 2006)
Background: Acne vulgaris is a common skin disease that involves pilosebaceous units. Oral antibiotics are the most widely administered drugs, which are prescribed as systemic therapy for treatment of moderate to severe acne vulgaris. Azithromycin is one of the antibiotics that has been recently used for acne treatment. There are several protocols of oral azithromycin in the treatment of acne. Objective: To compare three various regimens of oral azithromycin in the treatment of acne. Materials and Methods: Sixty-four patients with moderate to severe acne were divided into three groups randomly. First group (21 patients) received azithromycin as follow: five consecutive days, 500 mg on the first day and 250 mg daily for a further four days per month. Second group (22 patients): 500 mg daily for four consecutive days per month and the last group (21 patients): 250 mg daily thrice weekly. After the baseline visit, patients were scheduled to return at four-weekly intervals among 12 weeks. Result: There were no differences between three groups in decreasing of acne grading score. ( P >0.05). Efficacy of minimal dose was equal to maximum dose of azithromycin in treatment of acne. Oral azithromycin in all groups resulted in a significant decrease in acne grading score in each consecutive visit ( P < 0.001). Conclusion: Because of expensiveness of azithromycin,, we recommend azithromycin in low dose (1500 mg monthly) which is as effective as a high dose (3000 mg monthly) with lower cost, has more compliance and fewer side-effects.